Drug-related problems in the elderly - Midlv̲, Patrik. (Springer Netherlands, 2009)
The number of elderly is increasing in the developed part of the world. With increasing age the prevalence of many diseases will increase. This promotes high use of drugs. For all health care professionals, it is essential to be aware of the possible risks and difficulties with drugs in the elderly. In this book, the authors describe these difficulties from several aspects. Evidence based medicine and elderly, physiological alterations with age that affects pharmacology, specific conditions and drugs that are troublesome in the elderly as well as organisational shortcomings are covered. The authors are pharmacist and physicians and active as researchers, university teachers, and practitioners, with special focus on drugs in the elderly. They describe problems, but also possible solutions and aids in the pharmacotherapy of elderly. Drug-related problems in the elderly is written as a teaching text for students in different courses in the fields of pharmacology or geriatrics. It is also intended to serve as a source of information and clinical support in geriatric pharmacotherapy for students as well as all health care professionals, e.g. physicians, nurses and pharmacists.